Regulatory Impact Analysis: Regulasi Pasar Modern di Kabuoaten Bantul - Hudiyanto Hudiyanto; Nunuk Dwi Retnandari (Magister Ilmu Administrasi Publik, 2012)
RIA or Regulatory Impact Analysis is an analysis tool that is used to develop the quality of rules or policy that is made by the Government. This article is analyzing the use of RIA that is currently being run by Bantul Government in managing he moern market that is threatening the very existence of local economy that is currently the backbone of bantul's people economical activities. Th analysis, it's found out that the most threatened business by modern market is grocery stores, but the Bupati Rules limits the definition of local economy to traditional markets, which means that this Bupati Rules isn't consistent in protecting local economy. The modern market has an oligopoly structure. This kinds of structure make benefit the consumer, but on the other side, it also impose the transaction fee to the supplier. Bupati Rules that only manages the existence of modern markets become inefficient in removing the negative impact of the modern market itself. In the structure of market with that strong network, policy that only obstruct would be ineffective, because once the permission is granted, the network will spread by any means necessary. The protection to local economy bargaining position to the consumer and seller.